Adapting L-PBF process for fine powders: a case study in 420 stainless steel. Issue 11 (18th August 2022) - Nath, Subrata Deb; Okello, Alfred; Kelkar, Rajendra; Gupta, Gautam; Kearns, Martin; Atre, Sundar V.
ABSTRACT: The laser-powder bed fusion (L-PBF), also known as selective laser melting (SLM), is widely processed to a narrow powder size of 15 (D10 ) to 45 (D90 ) µm. However, expanding the particle size distribution (PSD) that can be processed by L-PBF can have important technical and economic benefits. Using 420 stainless steel as a case study, the current investigation successfully shows that finer particles can also be successfully processed by L-PBF to achieve comparable tensile strength, corrosion resistance, microstructure and density. The results of the study determined that agglomeration of fine powders was the critical barrier that previously limited successful processing. Further, the study clearly showed that a simple and scalable vibratory sieving process was sufficient to deagglomerate the fine powder to improve flowability and achieve consistent printability of engineering parts.